Food and the Social Identities of People with Learning Disabilities - Charlotte Aull Davies (Disability Studies Quarterly, 2007)
The behaviors surrounding food provision and consumption provide subtle, yet fundamental ways of defining social identities and structuring social relationships. The food consumption patterns of young adults with learning disabilities, and the control over their food consumption exercised by others, define them as 'children' even though they are physically and chronologically adults. These food-based behaviors contribute to the difficulties they face in achieving full social adulthood and thereby accentuate stigmatizing aspects of their social identities. Unsurprisingly, in some cases food becomes an area of conflict between these young people and their caregivers. Food provision also highlights a dilemma of the philosophy of care based on normalization theory, namely that actions taken to encourage age-appropriate behavior, and hence promote social adulthood in one sphere, may undermine adult identity in another. The paper is based on 18 months of participant observation and interviews with young adults with learning disabilities and their caregivers.
Keywords: food; identity; learning disabilities; learning difficulties; Intellectual disabilities; developmental disabilities; adulthood